The Role of Human Resources Practices in Enhancing Organizational Justice - Noor Arida Sofiana; Nur Rachmah Wahidah; Dean Herdesviana (Penerbit Goodwood, 2026)
Purpose: This study analyzes the influence of Recruitment and Selection (R&S) and Training and Development (T&D) on organizational justice. This study examines how these fundamental human resource practices collectively shape employees' perceptions of fairness in the workplace. Methodology: A quantitative approach was employed using survey methodology. Data were analyzed using multiple regression analysis to assess both the individual and combined effects of the independent variables on Organizational Justice. Results: The findings confirm that both Recruitment & Selection and Training & Development have significant positive effects on Organizational Justice. The results demonstrate that these human resource practices collectively explain a substantial proportion of the variance in fairness perceptions among employees. Conclusions: The study concludes that systematic Recruitment & Selection processes coupled with comprehensive Training & Development programs serve as crucial mechanisms for enhancing Organizational Justice. Organizations can strengthen employees' perceptions of fairness by implementing structured approaches to staffing and providing equitable access to development opportunities. Limitations: The main limitations include the cross-sectional nature of the data, which prevents the establishment of causal relationships, and the reliance on self-reported measures from a single source. This study also used a focused set of indicators for each construct. Contributions: Theoretically, this research validates the direct linkage between core HR functions and Organizational Justice perceptions. Practically, it provides organizational leaders with evidence-based guidance for leveraging recruitment and training systems as strategic tools to foster fair work environments.